1991
DOI: 10.2337/diacare.14.5.415
|View full text |Cite
|
Sign up to set email alerts
|

Infant Feeding in Finnish Children <7 yr of Age With Newly Diagnosed IDDM

Abstract: The protective effects of a long duration of breast-feeding and a late introduction of dairy products on the risk of IDDM remained significant after adjusting for the mother's education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
89
1
5

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(97 citation statements)
references
References 0 publications
2
89
1
5
Order By: Relevance
“…Risks of similar magnitude were observed 2 years later but the authors concluded that the relatively weak association between early exposure of cows' milk and the development of Type I diabetes might result from biases due to the methodological limitations of previous studies [9]. A Finnish case-control study reported an association between early exposure to cows' milk and an increased risk of Type I diabetes [10], independently of the duration of breastfeeding [11]. In immunological studies increased titres of cows' milk antibodies have been observed in children with newly diagnosed diabetes.…”
mentioning
confidence: 52%
“…Risks of similar magnitude were observed 2 years later but the authors concluded that the relatively weak association between early exposure of cows' milk and the development of Type I diabetes might result from biases due to the methodological limitations of previous studies [9]. A Finnish case-control study reported an association between early exposure to cows' milk and an increased risk of Type I diabetes [10], independently of the duration of breastfeeding [11]. In immunological studies increased titres of cows' milk antibodies have been observed in children with newly diagnosed diabetes.…”
mentioning
confidence: 52%
“…In previous studies, early introduction of cow's milk in infancy has been linked to the development of preclinical and clinical type I diabetes (Virtanen et al, 1991;Å kerblom et al, 2005). Findings from the randomized double-blind pilot trial suggest that the appearance of type I diabetesassociated autoantibodies can possibly be reduced by 40-60% by weaning high-risk infants to a highly hydrolyzed formula (Å kerblom et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Certain fatty acids function as biomarkers of milk and ruminant meat fat intake (Wolk et al, 2001), and essential fatty acids in serum reflect vegetable oil consumption (Zock et al, 1997). Cow's milk intake during infancy and childhood has been linked to development of type I diabetes (for example, Virtanen et al, 1991;Verge et al, 1994;Virtanen et al, 2000). We aimed at examining, in a birth cohort of children carrying increased human leukocyte antigen DQ b-1 (HLA-DQB1)-conferred risk for type I diabetes, what fatty acids in serum show association with the development of advanced b-cell autoimmunity, that is, positivity for islet cell autoantibodies (ICAs) and at least one other autoantibody out of the three additional antibodies commonly analyzed for predictive purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Siblings older than 14 years were excluded from the present analyses. In addition, birth-date-and sex-matched random population-based control children were collected from the Finnish national population registry for the 121 diabetic children younger than 7 years who were diagnosed from May 1988 to April 1989 [3]. Of these population-control children, 85 % participated in the dietary study and a blood sample was obtained in 87 %.…”
Section: Methodsmentioning
confidence: 99%
“…The results suggest that young age at introduction of dairy products and high milk consumption during childhood increase the levels of cow's milk antibodies and that high IgA antibodies to cow's milk formula are independently associated with increased risk of IDDM. [Diabetologia (1994) 37: 381-387] early introduction of dairy products or other foods could be related to an increased risk of IDDM [3][4][5][6][7]. A detailed study of infant feeding patterns indicated that the age at introduction of dairy products had the closest association with the risk of IDDM when the duration of both overall and exclusive breast-feeding was taken into account [8].…”
mentioning
confidence: 99%